The Importance of Teacher's Pedagogical Skills in Educating Primary School Students in the Spirit of Decency - Rabigʻa Shabatova (International Journal on Integrated Education, 2022)
This article focuses on the responsibilities of the primary school teacher in the learning process and the responsibilities he or she should have in relation to the child entering the first grade. The importance of educating primary school students in the spirit of morality is also emphasized, as is the need for the pedagogical skills of the primary school teacher.